2021
DOI: 10.3390/biomedicines9030255
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Insulin Resistance in Asymptomatic Patients with Acute Intermittent Porphyria and Liver-Targeted Insulin as a Novel Therapeutic Approach

Abstract: Acute porphyria attacks are associated with the strong up-regulation of hepatic heme synthesis and over-production of neurotoxic heme precursors. First-line therapy is based on carbohydrate loading. However, altered glucose homeostasis could affect its efficacy. Our first aim was to investigate the prevalence of insulin resistance (IR) in an observational case-control study including 44 Spanish patients with acute intermittent porphyria (AIP) and 55 age-, gender- and BMI-matched control volunteers. Eight patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…In the AIP context, it attempted to re-establish glucose homeostasis by activating hepatic gluconeogenesis and increasing mitochondrial mass, but it also induced ALAS1 expression [ 12 , 13 , 17 ], thereby exacerbating the porphyrins’ overproduction. In keeping with these findings, we found that the induction of fasting through glucose deprivation halved PBGD enzymatic activity at 50% and sensitized siPBGD cells to upregulate ALAS1, likely via PGC1α, without increasing heme production, similar to what has been reported in AIP rodents and patients exposed to precipitating factors [ 10 , 16 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the AIP context, it attempted to re-establish glucose homeostasis by activating hepatic gluconeogenesis and increasing mitochondrial mass, but it also induced ALAS1 expression [ 12 , 13 , 17 ], thereby exacerbating the porphyrins’ overproduction. In keeping with these findings, we found that the induction of fasting through glucose deprivation halved PBGD enzymatic activity at 50% and sensitized siPBGD cells to upregulate ALAS1, likely via PGC1α, without increasing heme production, similar to what has been reported in AIP rodents and patients exposed to precipitating factors [ 10 , 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…The binomial association between porphyrins and acute neuropsychiatric attacks has been at the basis of AIP pathogenesis for decades. Still, there are several reports that cast doubt about the exclusive pathogenic role of heme precursors in disease, as AIP patients who accumulate ALA and PBG may not manifest any acute attack throughout their life [ 16 , 22 ]. Thus, other factors may be involved in the pathophysiology of the acute event.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations